Perception of the local population regarding stray dogs in the Historic Center in the City of Cusco, Peru - Romero Quispe, Andrea (2023)
The study's objective was to determine the perception of the residents and merchants of the Historic Center of the City of Cusco about the presence of stray dogs in the city. The study corresponded to cross-sectional descriptive observational research. The data collection instrument considered the respondent's demographic information, the perception of stray dogs as a problem, and the respondents' opinion about workable solutions and those responsible for applying them. The information obtained was transferred to an Excel database and analyzed using descriptive and inferential statistics. A total of 400 people were surveyed (200 residents and 200 shopkeepers). Sixty-six percent of the residents and 64% of the shopkeepers indicated that stray dogs were a problem. 58.5% of the residents and 38% of the shopkeepers felt that most of these dogs had an owner. In addition, 53.5% of the merchants reported having received complaints from their customers due to the presence of these dogs. For those surveyed, the main problems caused by the presence of stray dogs in the city were the following: they litter the streets (51.5%), affect tourism (40.8%), and produce noise pollution (40.5%). According to those surveyed, the municipalities (50.3%) and the Ministry of Health (19.8%) should be responsible for this problem. The solutions proposed for this problem were the sterilization of females and castration of males (41 %), euthanasia (15.8 %), and pet identification (13.8 %). It is hoped that the results will be helpful in the implementation of a comprehensive program for responsible pet ownership at the study site.